Measurement of radon and uranium concentration in soil samples from Babylon cement plant using nuclear track detector CR-39 - Ahmed, Israa Kamil (Iraqi Journal of Physics, 2019)
In this study, concentrations of radon and uranium were measured for twenty six samples of soil. The radon concentrations in soil samples measured by registrant alpha-emitting radon (222Rn) by using CR-39 track detector. The uranium concentrations in soil samples measured by using registrar fission fragments tracks in CR-39 track detector that caused by the bombardment of U with thermal neutrons from 241 Am-Be neutron source that has flux of 5 ×103n cm-2 s-1.The concentrations values were calculated by a comparison with standard samples The results show that the radon concentrations are between (91.931-30.645Bq/m3).The results show that also the uranium concentrations are in soil samples under 0.051-0.0079ppm.